Primary blast lung injury at a NATO Role 3 hospital. Issue 2 (24th January 2014) - Aboudara, Matthew; Mahoney, P F; Hicks, B; Cuadrado, D
Abstract : Background: Primary blast lung injury (PBLI) is defined as lung contusion from barotrauma following an explosive mechanism of injury (MOI). Military data have focused on PBLI characteristics following evacuation from the combat theatre; less is known about its immediate management and epidemiology in the deployed setting. We conducted a quality improvement project to describe the prevalence, clinical characteristics, management strategies and evacuation techniques for PBLI patients prior to evacuation. Methods: Patients admitted to a Role 3 hospital in southwest, Afghanistan, from January 2008 to March 2013 with a blast MOI were identified through the Department of Defense Trauma Registry; International Classification of Diseases 9 codes and patient record review were used to identify the PBLI cohort from radiology reports. Descriptive statistics and Fishers exact test were used to report findings. Results: Prevalence of PBLI among blast injured patients with radiology reports was 11.2% (73/648). The population exhibited high Injury Severity Scores median 25 (IQR 14–34) and most received a massive blood transfusion (mean 33.4±38.3 total blood products/24 h). The mean positive end expiratory pressure (PEEP) requirement was 6.2±3.7 (range 5–15) cm H2 O and PaO2 to FiO2 ratio was 297±175.2 (66–796) mm Hg. However, 16.6% of patients had a PaO2 to FiO2 ratio <200, 13.3% required PEEP ≥10 cm H2 O and one patient required specialised evacuation for respiratory failure. A dismounted MOI (72.8%) and evacuation from point of injury by the Medical Emergency Response Team (62.3%) appeared to be associated with worse lung injury. Only eight of the 73 PBLI patients died and of the five with retrievable records, none died from respiratory failure. Conclusions: PBLI has a low prevalence and conventional lung protective ventilator management is generally appropriate immediately after injury; application of advanced modes of ventilation and specialised evacuation assistance may be required. PBLI may be a marker of underlying injury severity since all deaths were not due to respiratory failure. Further work is needed to determine exact MOI in mounted and dismounted casualties.